PERAN BIOSKOP SEBAGAI LITERASI WISATA DAN SPASIAL: PENGALAMAN DAN PEMAHAMAN MAHASISWA MELALUI SINEMA - Subhani, Armin; Nurabrori, Ahmad Subhan (Universitas Hamzanwadi, 2025)
The role of cinema as an entertainment medium is widely known, but it is not fully understood how the experience of watching films in cinema can affect tourist and spatial literacy in individuals. For this reason, this research aims to describe how cinema contributes to encouraging tourist and spatial literacy for students. Data were collected through questionnaires and direct observation of the experience of watching films in cinemas. Respondents involved 32 students who had viewing experience. The frequency of viewing is quite high, 1-2 times/month, indicating that cinema is still considered valuable and gives a different impression compared to watching at home. Action genre films are the most popular, namely 37.5% higher than other film genres. A total of 43.8% of respondents rated their understanding of tourism and spatial literacy, improved through the films they watched. Furthermore, 37.5% thought that films in cinemas depict the authentic tourist experience very well, and 40.6% of respondents felt that films in cinemas tell the history and cultural heritage of a destination very well or well. The majority of respondents, 87.5% agreed that the films made a positive contribution, while 12.5% were unsure. In conclusion, cinema can influence and enrich the audience's knowledge of tourist attractions and spatial dynamics. This research also confirms and strengthens the findings and theories in previous research, that films can function as educational tools for students.